Analisis Kredit Macet pada Kredit Usaha Rakyat (KUR) PT. Bank Rakyat Indonesia (Persero) Tbk Unit Rungkut Surabaya pada Masa Pandemi Covid-19 - Arsya Cheline Rafaella; Budi Prabowo (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
COVID-19 pandemic is a phenomenon that has made all economic sectors down, and thats including the banking sector. This pandemic makes credit risk will increase, therefore the problem in this research its about causes of bad credit in People's Business Credit (KUR), and how are the efforts of BRI Rungkut Surabaya Unit in resolving and minimizing bad loans during the Covid-19 pandemic. This study using qualitative research with a descriptive approach, informed by informants from BRI KUR Rungkut officers and KUR debtors as well as data on bad credit financial reports. The results showed that bad loans at BRI Unit Rungkut Surabaya were caused by external factors in the form of business risks, natural and non-natural disasters, and bad faith from customers. Internal factors in the form of overcrediting, analysis errors, and feelings of pity. The steps to resolve and minimize bad loans carried out by BRI Unit Rungkut Surabaya are in accordance with the regulations given by the government during the Covid-19 pandemic.